Clinical features in four patients with Angelman syndrome resulting from paternal uniparental disomy. Issue 5 (May 1997) - Smith, A; Marks, R; Haan, E; Dixon, J; Trent, R J
Abstract : Angelman syndrome (AS) is a complex neurological disorder with different genetic aetiologies. It is not known whether the clinical features vary depending on the genetic mechanism. We report four patients with AS owing to uniparental disomy (UPD). There were two males and two females, with a mean age of 8 years (range 7 to 11 years). All patients had a happy disposition, hyperactive behaviour, and the characteristic facial phenotype of AS, but in three there was a normal head circumference, two had epilepsy, ataxic movements were mild in three, the mean age of onset of walking was 2.4 years, and there was some sign language in all four patients. Our cases add further weight to the previously reported impressions of a milder phenotype in cases of AS resulting from UPD than in deleted AS patients. Patients suspected of having AS, but who are considered atypical, warrant DNA testing.